Not all autoantibodies are clinically relevant. Classic and novel autoantibodies in Sjögren’s syndrome: A critical review - Vílchez-Oya, Francisco; Balastegui Martin, Hector; García-Martínez, E.; Corominas, Hèctor (Frontiers in Immunology, 2022)
Sjögren’s syndrome (SjS) is a heterogeneous systemic disease. The abnormal responses to La/SSB and Ro/SSA of both B-cells and T-cells are implicated as well as others, in the destruction of the epithelium of the exocrine glands, whose tissue characteristically shows a peri-epithelial lymphocytic infiltration that can vary from sicca syndrome to systemic disease and lymphoma. Despite the appearance of new autoantibodies, anti-Ro/SSA is still the only autoantibody included in the American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) classification criteria and is used extensively as a traditional biomarker in clinical practice. The study and findings of new autoantibodies in SjS has risen in the previous decade, with a central role given to diagnosis and elucidating new aspects of SjS physiopathology, while raising the opportunity to establish clinical phenotypes with the goal of predicting long-term complications. In this paper, we critically review the classic and the novel autoantibodies in SjS, analyzing the methods employed for detection, the pathogenic role and the wide spectrum of clinical phenotypes.